Die Grenzen der Bukolik - Krupp, József (Acta Classica Universitatis Scientiarum Debreceniensis, 2025)
Szilárd Borbély (1963–2014) wrote long narrative poems in the last years of his life. The poems and the novel Nincstelenek (The Dispossessed, 2013) depict the life of a family in an East Hungarian village during the author's childhood years. In constructing the literary landscape, Borbély draws on ancient myths to paint a hierarchical picture of the village from a socio-economic perspective. Borbély planned to publish the poems under the title Bukolikatájban. Idÿllek (In a Bucolic Land. Idylls), although these are rather a palinody of a pastoral idyll. This essay examines how Borbély uses the word "gods" in the poems. Two poems (The Deucalion Collective Farm, Echo on the Veranda) serve as examples to show the role the reception of myth played in the construction of the "bucolic" world.